Theory of affective pragmatics under biolinguistics - Zhuo, Li (Frontiers in Psychology, 2024)
This paper introduces a pioneering investigation into affective pragmatics through the perspective of Darwinian Biolinguistics, an interdisciplinary field at the nexus of biological and linguistic principles. Anchored in Darwin's theory of evolution and the latest developments in neurobiology, this study delves into the influence of biological factors--especially those pertaining to the brain's emotional processing on pragmatic communication. The research posits that human emotional responses, inherent in our biological constitution, profoundly influence the usage and interpretation of language in social interactions.